A whole blood monokine-based reporter assay provides a sensitive and robust measurement of the antigen-specific T cell response - Chakera, Aron; Bennett, S.; Cornall, R. (2011)
Background: The ability to measure T-cell responses to antigens is proving critical in the field of vaccine development and for understanding immunity to pathogens, allergens and self-antigens. Although a variety of technologies exist for this purpose IFN?-ELISpot assays are widely used because of their sensitivity and simplicity. However, ELISpot assays cannot be performed on whole blood, and require relatively large volumes of blood to yield sufficient numbers of peripheral blood mononuclear cells. To address these deficiencies, we describe an assay that measures antigen-specific T cell responses through changes in monokine gene transcription. The biological amplification of the IFN? signal generated by this assay provides sensitivity comparable to ELISpot, but with the advantage that responses can be quantified using small volumes of whole blood.Methods: Whole blood or peripheral blood mononuclear cells (PBMCs) from healthy controls and immunosuppressed recipients of solid organ transplants were incubated with peptide pools covering viral and control antigens or mitogen for 20 hours. Total RNA was extracted and reverse transcribed before amplification in a TaqMan qPCR reaction using primers and probes specific for MIG (CXCL9), IP-10 (CXCL10) and HPRT. The induction of MIG and IP-10 in response to stimuli was analysed and the results were compared with those obtained by ELISpot.Results: Antigen-specific T cell responses can be measured through the induction of MIG or IP-10 gene expression in PBMCs or whole blood with results comparable to those achieved in ELISpot assays. The biological amplification generated by IFN?-R signaling allows responses to be detected in as little as 25 µL of whole blood and enables the assay to retain sensitivity despite storage of samples for up to 48 hours prior to processing.Conclusions: A monokine-based reporter assay provides a sensitive measure of antigen-specific T cell activation. Assays can be performed on small volumes of whole blood and remain accurate despite delays in processing. This assay may be a useful tool for studying T cell responses, particularly when samples are limited in quantity or when storage or transportation is required before processing. © 2011 Chakera et al; licensee BioMed Central Ltd.